Dust Mites Population in Indoor Houses of Suspected Allergic Patients of South Assam, India. (18th May 2011) - Sharma, Dhruba; Dutta, B. K.; Singh, A. B.
Abstract : Background . In the present study, quality and quantity of indoor dust mites was evaluated at the residence of 150 atopic allergic patients from four different districts of South Assam. Methods . Suspected patients with case history of allergic disease were selected for indoor survey. Dust samples (500 mg) were collected from the selected patient's house and were analyzed using standard methods. Results . About 60% of the selected patients were found suffering from respiratory disorders and rest 40% from skin allergy. The dominant mites recorded from indoor dust samples were Dermatophagoides followed by Blomia, Acarus, and Cheyletus while Caloglyphus was recorded in least number. The distribution of mites on the basis of housing pattern indicates that RCC type of buildings supports maximum dust mite's population followed by Assam type (semi-RCC) buildings, and the lowest count was observed in wooden houses. Environmental factors like temperature, rainfall, and relative humidity are found to determine the indoor mite's population. Severity of allergic attack in some of the typical cases was found to be proportional to the allergen load of mites in the dust samples. Conclusions . The economic status, housing pattern, and local environmental factors determine the diversity and abundance of dust mites in indoor environment.